PENGEMBANGAN KETERAMPILAN GURU BAHASA INGGRIS MELALUI PELATIHAN POWTOON DAN BOOKCREATOR DI ERA PEMBELAJARAN DIGITAL - Rahayu Sugiharti, Dona; Pariyanto, Pariyanto; Noraisya Primandari, Puteri (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The training on the use of Powtoon and BookCreator aims to improve the skills of English teachers in utilizing digital technology for learning. Attended by 25 Madrasah Tsanawiyah teachers, this activity consists of two main sessions: making animated videos with Powtoon and compiling interactive e-modules using BookCreator. On the first day, participants learned to make learning videos with Powtoon and upload the results to YouTube. On the second day, the training focused on creating digital teaching materials using multimodal features in BookCreator, such as text, graphics, audio, and video. This training received a positive response from the participants, who were actively involved in the practice sessions and showed high motivation to develop their competencies in digital teaching. The evaluation showed a high level of satisfaction, with teachers feeling that this training was relevant and useful for their English teaching. This training helped them adapt technology in learning, which is expected to increase student participation and interest in class. The final results are learning videos and e-modules that are ready to be used in class as interactive teaching media.